Penetapan Anggota Panwaslu oleh Bawaslu: Analisis Putusan Mahkamah Konstitusi Nomor 11/Puu-Viii/2010 - Eddyono, Luthfi Widagdo (Mahkamah Konstitusi Republik Indonesia, 2011)
The Constitutional Court of Indonesia in Decision Number 11/PUU- VIII/2010 stated that the provisions regarding the recruitment of members of the Supervisory Committee for the Election must be nominated by the Provincial/District General Elections Commission is contrary to Article 22E Paragraph (1) and paragraph (5), and Article 28D Paragraphs (1) of the 1945 Constitution. Therefore, to ensure a fair legal certainty and avoid disruption of the elections, the nomination and appointment of members of Supervisory Committee for the Election is conducted by one institution, namely the General Elections Supervisory Body (Bawaslu) or Supervisory Committee for the Election. The decision contains two legal meanings. First, the view that the principle of checks and balances are not only connected with separation of power at the legislative branch, executive branch, and judiciary branch, but also the relationship between “supervisors and the supervised” that based on the proportional rationality inter-state relations. Second, the case number 11/PUU-VIII /2010 actually contain elements of the dispute between the two state institutions, namely the General Elections Commission and Bawaslu because not only related to the interpretation of norms, but also the fate of members of 192 Supervisory Committee Election that not recognized and approved by the General Elections Commission. The problem handled by Constitutional Court using judicial review case against the 1945 Constitution.